KEPEMIMPINAN NON MUSLIM DALAM AL-QUR’AN: ANALISIS STRUKTURAL FERDINAND DE SAUSSURE DALAM KAJIAN AYAT-AYAT MUWĀLAH AL-KUFFĀR - Thoriq, Thoriqotul Faizah; Musolli; Moh. Anwari (Qolamuna : Jurnal Studi Islam, 2023)
This article aims to discuss the meaning of the word awliya' in the context of the closeness between Muslims and non-Muslims in the Qur'an. Through Ferdinad de Saussure's structural analysis knife, this paper focuses on the problem; how is the dissection of the meaning of awliya' in the view of de Saussure's structural semiotics? Is it true that Muslims, especially in Indonesia, cannot elect leaders who are non-Muslims? This article concludes that through de Saussure's structural theory, it is found that the word awliya' still opens up various meanings depending on the structure that surrounds the reader and researcher of this verse. Furthermore, with de Saussure's concept of signifiers, this article presents the fact that Muslims' attitude towards non-Muslims is not always in a negative dimension, in which case certain criteria are mentioned for non-Muslims who are allowed to cooperate or be friends. with Muslims. Keywords : Ferdinand De Saussure, Muwālah Al-Kuffār, Nonmuslim